2012
DOI: 10.1590/s0044-59672012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico da qualidade da água do rio Parauapebas (Pará - Brasil)

Abstract: ResumoO objetivo desta pesquisa foi desenvolver um diagnóstico da qualidade da água do rio Parauapebas (Estado do Pará, Brasil), com base no monitoramento realizado nos períodos de baixa precipitação dos anos 2004, 2007 e 2009. Em 20 locais de amostragem ao longo do rio no entorno da cidade de Parauapebas, foram avaliados na água parâmetros físicos (transparência, temperatura da água e resíduo total), químicos (oxigênio dissolvido, pH, turbidez, alcalinidade, dureza, acidez, cloreto, DBO, DQO e fósforo, ferro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 10 publications
1
5
0
20
Order By: Relevance
“…Values lower than 6.0 were also determined at spring points P8, P9, P10, P11, P12, P13, P14, P15 and P16 due to the presence of domestic and agricultural waste near the water. The variation coefficient of 12.5 % indicates that the pH in the natural environment of the drainage basin studied is the result of anthropogenic activities, which is in agreement with studies conducted in other drainage basins (Siqueira et al, 2012).…”
Section: Environmental Management and Sustainable Developmentsupporting
confidence: 89%
“…Values lower than 6.0 were also determined at spring points P8, P9, P10, P11, P12, P13, P14, P15 and P16 due to the presence of domestic and agricultural waste near the water. The variation coefficient of 12.5 % indicates that the pH in the natural environment of the drainage basin studied is the result of anthropogenic activities, which is in agreement with studies conducted in other drainage basins (Siqueira et al, 2012).…”
Section: Environmental Management and Sustainable Developmentsupporting
confidence: 89%
“…The trend to acidity was associated with organic matter decay by Blume et al (2010) (6.8-7.3) in the Sinos River basin (Rio Grande do Sul State); Siqueira et al (2012) , 2013 correspond to rainy days, with consequent higher river discharges. In accordance with Crispim et al (2012), another factor that has contributed to increased turbidity in the Campo River, averaging 30 -40 NTU, is the transport of sediments from the overflow of retention boxes filled with eroded soil, from compaction and preparation for sowing, towards the slope, and from rill erosion on roadsides by the poor maintenance of rural roads.…”
Section: Resultsmentioning
confidence: 92%
“…These values were superior in 16.7%, 41.7%, 83.3% and 91.7% at P1, P2, P3 and P4, respectively, relative to the limit of 1,000 MPN/100 mL set by the Conama Resolution 357/2005 (Brasil, 2005). Likewise, Rocha et al (2006) found values 63% higher than the standard in a rural area; Siqueira et al (2012) recorded values from 200 to 1,300 MPN/100 mL in an urban area. Figure 5 illustrates the temporal variation of dissolved oxygen (DO), from 5.86 to 9.3 mg/L, 7.6 to 9.3 mg/L, 5.8 to 9.4 mg/L and 7.0 to 9.2 mg/L at P1, P2, P3 and P4 sites, respectively, that is, above the limit of 5.0 mg/L of the Conama Resolution 357/2005 for Class 2 (Brasil, 2005).…”
Section: Resultsmentioning
confidence: 93%
“…As águas da região possuem características ácidas, em virtude da contribuição da área da bacia hidrográfica e da decomposição de material orgânico do ambiente em compostos ácidos, responsáveis pelos baixos valores de pH encontrados também nos solos (SIOLI, 1976;SIQUEIRA et al, 2012). Portanto, em relação ao pH, as águas estariam em desconformidade com a legislação vigente, considerando-se a Resolução Conama nº 357/05, contudo os valores refletem condições naturais da região.…”
Section: Discussionunclassified